Farmer’s attitude towards the productivity of rice in PPK Jaya Peringat, Kelantan / Norsuliyana Mohd Noor - Mohd Noor, Norsuliyana (Faculty of Plantation and Agrotechnology, 2019)
Rice, Oryza sativa is one of the common crops in the Malaysia that also as a staple food for humans. Attitudes are one of the aspects that affect the rice productivity of farmers. Mostly the farmers misunderstanding their attitudes, whether it relates or not towards the productivity of rice yield The objectives of this study are to examine the relationship between the attitudes with rice productivity of farmers. And to determine the most dominant of attitude factor that affect the productivity of farmers. This study was conducted on 92 respondents that comes from the farmers under the Pertubuhan Peladang Kawasan (PPK) Jaya Peringat, Kelantan. Data were collected by well-structured and reliable questionnaires. The independent variables for this study consists attention to farming practices, openness to ideas, stress behavior and lastly is risk taking. While, independent variables in this study is the rice productivity of farmers. Two analysis testing used in this study to achieve the objectives which are correlation analysis and multiple linear regression. From the correlation analysis, the results show that the attitude factor which is stress behaviour gives the positive strong relationship (0.606) on the rice productivity. Meanwhile, for the multiple linear regression, openness to ideas is the most dominant attitude factor that affects the productivity of farmers. As a conclusion, attitude factor of openness to ideas play an important role towards the rice productivity of farmers. A suggestion to improve the rice productivity of farmers for the agricultural government sector, extension officers should consider attitudes of farmers when dealing with development strategies or training programs in order to achieve strong farmers’ cooperation.